Social Media as Promotion of Dental and Oral Health in Adolescents - Pindobilowo; Disson Muhammad Fauzi; Adiella Yangkie Lubis; Henny Wahyuningsih (Formosa Journal of Applied Sciences, 2023)
Introduction: Adolescents often use social media in their daily activities, social media can potentially be a medium for delivering behavior change interventions and also has the potential to help improve dental and oral health for adolescents. Purpose: to conduct a literature review that examines the use of social media as a promotion of oral health in adolescents. Method: This literature study uses the Narrative Review method. References were collected in the form of journals through the online database and website of BMC Oral Health, PubMed, Wacana and Google Scholar. References were also selected through reference analysis in the form of research, articles and systematic reviews. Conclusion:. Social media is one of the educational tools used in knowledge about oral health in society, especially in adolescents